If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = -9y + 3x Reorder the terms: -27 = 3x + -9y Solving -27 = 3x + -9y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -27 + -3x = 3x + -3x + -9y Combine like terms: 3x + -3x = 0 -27 + -3x = 0 + -9y -27 + -3x = -9y Add '27' to each side of the equation. -27 + 27 + -3x = 27 + -9y Combine like terms: -27 + 27 = 0 0 + -3x = 27 + -9y -3x = 27 + -9y Divide each side by '-3'. x = -9 + 3y Simplifying x = -9 + 3y
| 8c*3=48 | | -5(X+4)-44=8-32 | | X^2=4.8 | | 55=2.50x-10 | | 1/5y+7=3 | | 5[7-(1+2)(1+2)]= | | n(17-9)+9=17 | | 15a-3b+12c-5a+b-10c= | | d+2*2=4d-2 | | 1.72*5(2)= | | 3x+18+93=90 | | c=600+60n | | 21-47=3(X-2)-8 | | y^6-4y^3=0 | | 9x-x-5x=260 | | 4x+2=10x | | P=4g+8 | | 2x^2-9=25 | | 6=1.199x+b | | j*3.87=7 | | 2sin^2x=2-cosx | | H(t)=-16t^2+96t+180 | | 1/4x+5=3 | | 2z=14-26 | | 7+x+13=25 | | 45+16lnx=50 | | 3p*(-3)=36 | | 1+2v=7 | | ln(4x)=0.5 | | 17-x=2(x+2)3 | | 0=25x^2+5x | | 2x-14=-72 |